Abdurrahman Wahid's Cosmopolitanism in the Protection of Religious Freedom in Indonesia: Policy Analysis and Implementation Challenges - Difa Meetia Putri (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
Indonesia as a pluralistic country faces challenges in ensuring religious freedom in the midst of ethnic, cultural, and religious diversity. Although various studies have discussed pluralism and are associated with the thought of Abdurrahman Wahid (Gus Dur), studies that specifically link the concept of cosmopolitanism with the implementation of public policies in the protection of religious freedom are still limited. This research aims to analyze the concept of Gus Dur's cosmopolitanism and its implementation in public policy and the challenges faced in the context in Indonesia. This research uses a qualitative approach with a literature study method, utilizing primary sources in the form of Gus Dur's writings and policies as well as secondary sources from relevant academic literature. Data analysis was carried out through content analysis techniques to interpret Gus Dur's ideas and policies in the socio-political context of Indonesia. The results of the study show that Gus Dur's cosmopolitanism is reflected in concrete policies such as the revocation of discriminatory regulations against the Confucian community and his defense of minority groups. However, the implementation of these values faces structural, political, and cultural challenges. This research confirms that Gus Dur's cosmopolitanism is relevant as a normative foundation in strengthening democracy and tolerance in Indonesia.